2008
DOI: 10.1071/ea08120
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for bodyweight, wool, and disease resistance and reproduction traits in Merino sheep. 2. Genetic relationships between bodyweight traits and other traits

Abstract: The Australian Merino is the predominant genetic resource for both the prime lamb and sheep meat industries of Australia. There are very few studies that provide good information on the relationships between wool and non-wool traits. The objective of this paper was to describe genetic relationships within bodyweight traits and between bodyweight and other traits recorded in Merino sheep. The genetic correlation between bodyweight, fleece weight and fibre diameter was positive (0.1 to 0.2). While fibre diameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
30
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 9 publications
12
30
4
Order By: Relevance
“…This contradicts previous findings from smaller studies where PWWT had no effect , though it does support the general principle that lambs selected for high post weaning weights would have a larger mature size (Huisman & Brown, 2008) and therefore they will be physiologically less mature when compared at the same weight (Berg & Butterfield, 1968;Butterfield et al, 1983;Hegarty, Shands, et al, 2006) …”
Section: Pwwt Asbvcontrasting
confidence: 57%
See 3 more Smart Citations
“…This contradicts previous findings from smaller studies where PWWT had no effect , though it does support the general principle that lambs selected for high post weaning weights would have a larger mature size (Huisman & Brown, 2008) and therefore they will be physiologically less mature when compared at the same weight (Berg & Butterfield, 1968;Butterfield et al, 1983;Hegarty, Shands, et al, 2006) …”
Section: Pwwt Asbvcontrasting
confidence: 57%
“…This change in body composition may be suggestive of low PFAT animals having a larger mature size, however, previous research has demonstrated little genetic or phenotypic correlation between sire PFAT and adult weight (Huisman & Brown, 2008) or growth rate (Kelman et al unpublished). Thus it seems likely that these compositional differences will still be present when the animals reach their mature size.…”
Section: Pfat Asbvmentioning
confidence: 74%
See 2 more Smart Citations
“…This was a reflection of their greater lean weight across all three carcass sections compared to both Merino and Maternal sired lambs, consistent with their larger mature size and therefore reduced maturity when compared at the same weight (Huisman & Brown, 2008). On the basis of these differences the carcasses of Terminal sired lambs were worth $9.57 and $14.36 more than the Merino and Maternal sired lambs.…”
Section: The Impact Of Sire Type and Dam Breed On The Value Of The Lamentioning
confidence: 71%